MODEL DESAIN PERKERASAN DAN PEMBIAYAAN RUNWAY BANDAR UDARA REMOTE AREA DENGAN METODA CBR DAN FAA - Zia Ahmad Riyanto, Fakri; Irfan Rifai, Andri (Universitas Majalengka, 2019)
The increasing on air transportation passengers and the development of the remote area are factors that accelerate the needed develop of runway pavements. The research aims to find out how to design flexible pavement for runway with two methods, that is CBR (California Bearing Ratio) method and FAA (Federal Administration Aviation) method. Thick of pavement evaluated with PCN-ACN (pavement classification number) method. The designs included a range of subgrade conditions, as well as commercial aircraft and analyzed optimal budget. Case study in the research is Andi Jemma Airport, South Sulawesi. Based on analysis result from the two methods obtained the thick of pavement with CBR method is 21 inch with PCN 27,9 F/C/X/T, thick of pavement with FAA graphic method is 17,5 inch with PCN F/C/X/T and from software FAARFIELD the thick of pavement is 16 inch with PCN 16,9 F/C/X/T. The cost required for thick of pavement analyzed by CBR method is IDR 6.415.252.926, with FAA graphic method is IDR 5.897.401.963 and with the FAA software FAARFIELD is IDR 5.675.465.836. These results indicate that the models obtained for FAA (software) can be used to design the pavement, where as it optimal budget.